A new gecko (Phyllodactylidae: Homonota whitii group) from the Diaguita highlands, Argentina, with an updated phylogeny for the genus - Morando, Mariana; Sánchez, Kevin I.; Vrdoljak, Juan E.; Pérez, Cristian H. F.; Sites, Jack W.; Avila, Luciano J. (Zoologica scripta, 2025)
The South American Transition Zone (SATZ) connects the Neotropical and Andean regions, stretching from western Venezuela to northern Chile and central‐western Argentina. In Argentina, the northwestern Altoandina Cuyana province includes arid and semi‐arid ecosystems, particularly the Diaguita District, spanning Catamarca, La Rioja and northern San Juan. This mountainous region, including the Sierra de Famatina and Cordillera Frontal de los Andes, hosts species adapted to extreme conditions. Despite its biodiversity, the region's endemicity and phylogenetic uniqueness remain poorly understood, especially as these ecosystems face growing climate threats, such as heatwaves. Geckos (Order Gekkota) are one of the oldest lizard clades, with divergences over 150 million years ago. Particularly, the genus Homonota (Phyllodactylidae) is endemic to the southern cone of South America, primarily in Argentina, with species also found in Brazil, Paraguay, Bolivia and Uruguay. As part of a broader investigation on geckos of this genus and to advance their systematic study, we generated data from two mitochondrial and 12 autosomal loci across 14 species, along with a comprehensive morphological dataset of meristic measurements and scale counts. Detailed analyses were conducted within an integrative species assessment framework. Consequently, we describe a new species of Homonota from the Diaguita biogeographic district in northwestern Argentina, representing the northernmost member of the H. whitii group. The species inhabits a mountainous region known for its micro‐endemism, further highlighting the area as an important biodiversity hotspot for dryland ecosystems. Additionally, we provide an updated molecular phylogenetic hypothesis for the genus, offering new insights into the evolutionary history within Homonota and the broader biodiversity of the SATZ.